Estudo da evolução do perfil de tensões residuais em solda multipasse do aço API 5L X65 - Cruz Neto, Raimundo Quindere (2018)
The current paper has the objective to analyze the residual tension profile on the welded joints of the API 5L X65 steel, on the transversal and longitudinal directions, identifying the critical points close to the root face and the weld face. For this study two wending processes were used in the specimens: For the root pass it was used the Shield Metal Arc Welding (SMAW) process. For the hot passes, the filling passes and the cover pass it was used was the Gas Metal Arc Welding (GMAW) process. After the obtainment of the specimens the residual tensions were analyzed by the X-Ray diffraction method. It was observed for the transversal direction an inversion of the p residual tensions profile, furthermore, the same was observed for the longitudinal direction. On the root pass there was a predominant tractive profile for the transversal direction with tensions up to 280 Mpa, those were reverted to compressive tensions on the order of 165 Mp. For the longitudinal direction the traction tensions of 400 Mpa were inverted in compression tension on the order of 125 Mpa. The tension profile generated near the face of the weld did not suffer from tractive to compressive inversion. The critical points are mainly located by a distance between 4 to 8 mm from the central fusion line.